PENERAPAN JOYFUL LEARNING PADA PEMBELAJARAN MATEMATIKA DI MI NU NURUL HAQ - Intan Nurmala Putri; Rizal Kurniawan; Deshiva Alifh Aulia Reishmana; Dian Mustika Anggraini (PHI: Jurnal Pendidikan Matematika, 2026)
This study aims to examine the implementation of joyful learning in mathematics instruction and to assess its effects on students’ motivation and learning outcomes at MI NU Nurul Haq Kudus using a descriptive qualitative approach involving a teacher and 27 fourth-grade B students as research participants. Data were collected through observation, interviews, and documentation, and then analyzed using the Miles and Huberman framework, which includes data reduction, data display, and conclusion drawing. The findings reveal that the application of joyful learning can foster a more engaging, interactive, and varied classroom atmosphere through the use of educational games, songs, and technology-based media, while also promoting students’ active participation in the learning process. As a result, students demonstrate increased enthusiasm, greater confidence, and improved motivation and academic achievement, particularly in learning pictogram material. However, several challenges remain, including differences in students’ abilities, the presence of misconceptions, and limited instructional time. Therefore, teachers are encouraged to continuously develop creative teaching innovations, apply differentiated instruction, and enhance students’ conceptual understanding through contextual approaches to achieve more optimal learning outcomes.